Orthodox Mobilizations and Political Identities in Post-Soviet Georgia - Serrano, Silvia (Journal of religion in Europe, 2021)
Based on field research carried out over the last two decades, this article analyzes the labile nature of the relationship between religion and politics in Georgia. It aims to understand not only the rational and deliberate processes in which elites engage for political ends but also to grasp the diversity of actors and patterns of religion mobilization. It argues that three main types of articulations have developed since the 1990s: the mobilization of Orthodoxy (1) in the service of nation-building; (2) in the construction of an anti-elite popular identity; and (3) as a moral crusade. Each type of articulation involves specific social actors, organizational forms, and relations with political institutions.